Risk Analysis of H2S Gas Exposure at Benowo Landfill Surabaya - Herman Bagus Dwicahyo1, Lilis Sulistyorini2, Abdul Rohim Tualeka1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Air pollution can be caused by the number of dangerous gases that arise due to the process of accumulating decaying waste which has acute and chronic effects for people who are exposed. Judging from the data collection method, this study is observational. The study design used in this study was a cross-sectional study design. Risk agent toxicity is expressed in reference doses. For non-carcinogenic inhalation exposures expressed by the Reference Concentration (RfC). Based on primary data derived from the results of measurements of ambient air quality at the loading terminal IIB TPA Garbage Surabaya, the results showed that H2S gas levels of 0.04 where the levels are still below the ambient air quality standards based on East Java Governor Regulation No. 10 of 2009 concerning Quality Standards Air Ambient. From the calculation above, the researcher took the safe value by choosing the cancer risk safe value from the calculation data most likely to be applied by scavengers in the TPA Sampoerna Benowo Surabaya, namely C safe at 3 mg / m3, safe for 3 hours/day and safe for 2 years. Preventive efforts that can be carried out are by controlling the source such as not doing landfill with the open dumping method using the sanitary system. Routinely monitor and control emissions, so that the air quality around the waste picker environment is maintained. Reducing the number of exposures by using personal protective equipment (PPE) in the form of respirators (masks). Perform administrative control by reducing the time and frequency of exposure to H2S dangerous gases. It is better for the Surabaya government and PT X to socialize the hazards and impacts of H2S exposure to workers.